Uji Efektivitas Antibakteri Handsanitizer Minyak Atsiri Kalamansi (Citrofortunella Microcarpa) Terhadap pertumbuhan Escherichia coli dan Staphyllococcus Aureus Secara In Vitro - Aina Fatkhil Haque; Betna Dewi; Dika Amanda (Politeknik Medica Farma Husada Mataram, 2021)
This study aims to determine the antibacterial activity, effective concentration, and the effect of increasing the concentration of Kalamansi orange essential oil in Handsanitizer gel on the inhibition of growth of Eschericia coli and Staphyllococus Aureus bacteria. Testing for antibacterial activity using the agar cakram method. The parameter that is measured is the diameter of the resistivity formed around the disc paper. Antibacterial activity test results were analyzed by descriptive method. The results showed that the concentration of essential oil in the Handsanitizer gel was 1%; 2%; and 4% have provided inhibitory activity for the growth of the tested bacteria. Effective concentration that can inhibit Eschericia coli and Staphyllococus Aureus bacteria at a concentration of 4%. The increase in the concentration of kalamansi orange essential oil showed the wider the diameter of the inhibition zone for bacterial growth. The inhibition that occurs in the Eschericia coli and Staphyllococus Aureus bacteria, proves that the Gel Handsanitizer Preparation Kalamansi orange essential oil contains limonene active compounds which are antibacterial. From the research that has been done, the following conclusions can be drawn: The availability of Kalamansi orange essential oil gel Handsanitizer with a concentration of 1%, 2% and 4% can inhibit the activity of the bacteria Eschericia coli and Staphyllococus Aureus in vitro. With the higher the concentration of kalamansi orange essential oil, the stronger the antibacterial inhibition is produced so that the handsanitizer with a concentration of 4% has the strongest antibacterial power against Eschericia coli and Staphyllococus Aureus bacteria.